2020
DOI: 10.1063/5.0012840
|View full text |Cite
|
Sign up to set email alerts
|

Many-body reactive force field development for carbon condensation in C/O systems under extreme conditions

Abstract: We describe the development of a reactive force field for C/O systems under extreme temperatures and pressures, based on the many-body Chebyshev Interaction Model for Efficient Simulation (ChIMES). The resulting model, which targets carbon condensation under thermodynamic conditions of 6500 K and 2.5 g cm−3, affords a balance between model accuracy, complexity, and training set generation expense. We show that the model recovers much of the accuracy of density functional theory for the prediction of structure,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 56 publications
3
27
0
Order By: Relevance
“…Similar to previous ChIMES studies 28,30,31 , we found that ChIMES force field stability is improved with the use of an iterative fitting scheme. The initial model is generated by fitting directly to configurations from DFT-MD simulations.…”
Section: A Model Details and Training Set Generationsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to previous ChIMES studies 28,30,31 , we found that ChIMES force field stability is improved with the use of an iterative fitting scheme. The initial model is generated by fitting directly to configurations from DFT-MD simulations.…”
Section: A Model Details and Training Set Generationsupporting
confidence: 86%
“…The ChIMES model is parameterized by matching to reference data for selected configurations which are taken from short DFT-MD trajectories. It has been shown that ChIMES models yield good agreement with DFT results for the structural, dynamical properties and/or the chemistry of molten carbon 28 , liquid water at ambient conditions 30 , and carbon monoxide at extreme conditions 31 .…”
Section: Introductionmentioning
confidence: 92%
“…Specifically, the two-body interactions are expressed as a linear combination of Chebyshev polynomials of the first kind In this case, T n ( s ij ) is the Chebyshev polynomial of the first kind of n th order, e i and e j are the element types of atoms i and j , and s ij is a transformation of the interatomic distance r ij over the Chebyshev interval of [−1,1] using a Morse-like function. In addition, Θ 2 corresponds to the two-body polynomial order, f C ij ( r ij ) is the cutoff function that ensures the potential and its derivative vary smoothly to zero beyond a specified distance, and f P ij ( r ij ) is a penalty function 13 , 17 that helps to prevent sampling of interatomic distances below those seen in the training set (see ref ( 18 ) for further details). is a set of permutationally invariant coefficients of linear combination for a given atom pair type that are determined via a linear least-squares method.…”
Section: Methodsmentioning
confidence: 99%
“…Modern machine learning (ML) force fields are providing additional options for computationally tractable chemically reactive simulations. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] . ChiMES is one such approach that has been applied to chemically reactive fluids.…”
Section: Introductionmentioning
confidence: 99%